Pengaruh Dompet Digital Terhadap Budaya Belanja Individu di Kota Medan - Purnama Ramadani Silalahi; Rindi Safira; Zsasa Aulia Hubara; Eka Purnama Sari (UNIVED Press, 2022)
Current technological developments are progressing quite rapidly, so that it affects the development of payment systems, especially in the use of non-cash payment systems. Non-cash payment systems have begun to replace the role of cash payment systems in Indonesia. The development of digital wallets continues to this day. The purpose of this research is to find out how the use of digital wallets affects individual shopping culture in the city of Medan. This study uses a qualitative method using a questionnaire with a sample of 100 people, and a test tool using SPSS 25. The results of this study indicate that there is an effect of using a digital wallet with individual shopping culture. The results of the R Square value of 0.827 indicate that trust, convenience and benefits of digital wallets have an influence of 82.7%, while the rest is influenced by other demand variables.